Feasibility of submerged floating tunnel with polygonal cross-sections — investigation from a viewpoint of submarine slide hazards - Fan, Ning; Hu, Yixuan; Wu, Hao; Li, Xiaobing; Jiang, Jianxiong; Xie, Jiacheng (Frontiers in Marine Science, 2023)
Recently, submerged floating tunnels have generated a lot of interest due to their unique cross-water traffic benefits. However, the destructive threat of submarine slide hazards was not fully considered in the design scheme of submerged floating tunnels, in particular to the feasibility of applying various cross-section forms on land to submerged floating tunnels under that hazard influence. This study mainly investigates the load effect of submerged floating tunnels with polygonal cross-sections (comprising three types: square, hexagon, and octagon) under the impact of submarine slides, via a computational fluid dynamics (CFD) approach. Results show that the impact forces produced by submarine slides on submerged floating tunnels are significant (e.g., submarine slides with a velocity of 4 m/s may produce a force level near 1×105 N/m), where the horizontal impact force components should be given priority consideration based on the general working environment of submerged floating tunnels. Compared with typical circle tunnels, polygonal tunnels suffer higher impact forces, and the polygonal types with fewer edges show a greater impact force. Finally, a simplified force evaluation approach for the submerged floating tunnel with polygonal cross-sections is proposed for guiding the relevant engineering design.